2016
DOI: 10.1111/jam.13202
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistantStaphylococcus aureusisolates from surfaces and personnel at a hospital laundry facility

Abstract: This is the first report of isolation and characterization of MRSA from surfaces and personnel from a clinical laundry facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…High touch surfaces were selected at the temple sites, which were areas that the primates often touched. Solid surfaces were swabbed with sponges to collect the bacteria on the surfaces as previously described (Michael et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…High touch surfaces were selected at the temple sites, which were areas that the primates often touched. Solid surfaces were swabbed with sponges to collect the bacteria on the surfaces as previously described (Michael et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…; Michael et al . ). Evans demonstrated that people might be infected with environmental viruses through different pathways (Evans et al .…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported the high incidence of these coliforms in wastewater from hospital laundries. 37,66,75 In this sense, the scientific community reports several cases of infection in hospital laundries: 65 rotaviruses, Clostridium difficile, 49,51,61 influenza virus (H1N1), 73 Streptococcus spp., 182 Enterococcus spp., 70,71 Acinetobacter spp., 69 Staphylococcus spp., 68,183 Pseudomonas, 67 Bacillus spp. 54 and hepatitis A virus.…”
Section: Characterization Of Laundry Effluentsmentioning
confidence: 99%